1999
DOI: 10.1007/s004210050488
|View full text |Cite
|
Sign up to set email alerts
|

Hypotension following mild bouts of resistance exercise and submaximal dynamic exercise

Abstract: Our purposes were (1) to examine resting arterial blood pressure following an acute bout of resistance exercise and submaximal dynamic exercise, (2) to examine the effects of these exercises on the plasma concentrations of atrial natriuretic peptide ([ANP]), and (3) to evaluate the potential relationship between [ANP] and post-exercise blood pressure. Thirteen males [24.3+/-(2.4) years] performed 15 min of unilateral leg press exercise (65% of their one-repetition maximum) and, I week later, approximately 15 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
80
6
22

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(121 citation statements)
references
References 29 publications
13
80
6
22
Order By: Relevance
“…[13][14][15] However, its occurrence in normotensive humans is inconsistent. Although we have found that PEH can be detected in normotensive individuals, 16 it was found to be much less consistent and of lesser magnitude than in hypertensive individuals. This may be due to other compensatory mechanisms, such as the baroreflex, that are activated in normotensive subjects, and prevent the degree of PEH from affecting orthostatic tolerance.…”
Section: Does Peh Occur In All Individuals?contrasting
confidence: 72%
See 4 more Smart Citations
“…[13][14][15] However, its occurrence in normotensive humans is inconsistent. Although we have found that PEH can be detected in normotensive individuals, 16 it was found to be much less consistent and of lesser magnitude than in hypertensive individuals. This may be due to other compensatory mechanisms, such as the baroreflex, that are activated in normotensive subjects, and prevent the degree of PEH from affecting orthostatic tolerance.…”
Section: Does Peh Occur In All Individuals?contrasting
confidence: 72%
“…Data from MacDonald et al 16 can often reach values of over 200 mm Hg. 2 Although it is usually reported that DBP changes little throughout changes in the exercise intensity, Palatini 3 has suggested that changes in DBP are more variable and can range from a slight decrease, due to the vasodilation of the muscle vasculature, to an increase of 10 to 20 mm Hg, presumably from the occlusion of blood flow caused by the forceful contractions of the exercising muscle.…”
Section: Endurance Exercisementioning
confidence: 98%
See 3 more Smart Citations